Reed fiber biomass full-degradable meal box and preparation method thereof
By generating titanium dioxide on reed cellulose and compounding with polyvinyl alcohol, blurring its interface with degradable plastic, the problem of non-degradable and poor performance of existing lunch box materials is solved, and high-performance and degradable lunch box is achieved Preparation improves the mechanical properties and degradation properties of the lunch box.
Patent Information
- Application Number
- CN202311114744.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2024-12-20
AI Technical Summary
Most of the existing disposable lunch boxes are non-degradable plastics, which lead to environmental pollution and poor performance. The interface effect between bio-based plastics and natural polymer materials leads to low product performance and inability to meet the usage requirements.
By compounding reed cellulose, titanium dioxide is generated and composited with vanillin-grafted polyvinyl alcohol, the interface between reed fibers and degradable plastic is blurred, and its fusion and mechanical properties are improved.
It improves the mechanical properties and water resistance of the lunch box, while enhancing the degradation properties of the degradable plastics. Through the antibacterial and photocatalytic effects of titanium dioxide, the safety and environmental friendliness of the lunch box are ensured.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic bag manufacturing, and in particular to a reed fiber biomass fully degradable lunch box and a preparation method thereof. Background Art
[0002] Plastics are very important organic synthetic polymer materials with a wide range of applications. Since the emergence of the world's first fully synthetic plastic in 1907, the plastics industry has developed rapidly, but while bringing benefits to mankind, it has also caused a series of environmental and resource problems. In particular, as takeout has entered people's lives, the use of disposable lunch boxes has greatly increased.
[0003] Existing disposable lunch boxes are generally made of non-degradable organic materials (such as expanded polystyrene, polyvinyl chloride, polyvinyl alcohol, etc.). Long-term use is not only harmful to the body, but also causes large-scale environmental pollution and becomes a global public hazard. There are also attempts to use paper, but paper materials have poor water and oil resistance. When used for lunch boxes, they are easy to become soft and cannot be used for a long time.
[0004] In the existing technology, the development of bio-based plastics and the utilization of renewable resources, as one of the effective measures to achieve sustainable development, have become a global research hotspot. Cellulose, starch, chitin and protein are all raw materials of natural polymer materials involved in scientists' research. The commonly used technology is basically to directly mix these natural polymer materials with degradable plastics for use. However, due to the interface effect between these natural polymer materials and degradable plastics, the final product performance is not high and cannot meet the corresponding use requirements. Summary of the invention
[0005] In view of the above problems, the purpose of the present invention is to design and provide a reed fiber biomass fully degradable lunch box and a preparation method thereof. By compositely modifying the reed cellulose, the interface between the reed fiber and the degradable plastic can be blurred, and the fusion of the two can be improved, thereby improving the performance of the lunch box.
[0006] The present invention solves the above technical problems by the following technical means:
[0007] A reed fiber biomass fully degradable lunch box, comprising the following raw materials in parts by weight: 200-250 parts of composite fiber, 650-700 kg of degradable plastic, 5-20 parts of lubricant, 20-40 parts of processing aid, and 25-100 parts of auxiliary materials. The composite fiber is obtained by using reed cellulose as a carrier, in-situ generating titanium dioxide on the reed cellulose, and then compounding with polyvinyl alcohol grafted with vanillin.
[0008] Furthermore, the gas pipeline comprises the following raw materials in parts by weight: the lunch box comprises the following raw materials in parts by weight: 220 parts of composite fiber, 650 parts of degradable plastic, 15 parts of lubricant, 25 parts of processing aid, and 40 parts of auxiliary materials.
[0009] Furthermore, the degradable plastic is any one of polybutylene adipate / terephthalate and polylactic acid.
[0010] Furthermore, the auxiliary materials include 5-45 parts of vinyl acetate and 15-60 parts of polyvinyl alcohol.
[0011] Furthermore, the processing aid includes 5-15 parts of antioxidant, 5-20 parts of dioctyl phthalate, and 8-15 parts of glycerol.
[0012] In addition, the present invention also discloses a method for preparing the above-mentioned reed fiber biomass fully degradable lunch box, which specifically comprises the following steps:
[0013] Extraction: The reeds are dried and ground into powder, and then the reed cellulose is extracted by acid-base method to obtain reed cellulose. Then, titanium dioxide is generated in situ on the reed cellulose using the reed cellulose as a carrier, and then composited with polyvinyl alcohol grafted with vanillin to obtain composite fibers.
[0014] Granulation: Add composite fiber, biodegradable plastic, lubricant, processing aid and auxiliary materials into a kneader, mix for 10 minutes, and then perform plasticization, extrusion and granulation in a single screw extruder to obtain biodegradable masterbatch;
[0015] Molding: The biodegradable masterbatch is compressed on a tablet press, and then the lunch box is formed by a blister machine.
[0016] Furthermore, the extrusion temperature in the single-screw extruder is 180-190° C., and the rotation speed is 30-60 r / min.
[0017] Furthermore, the preparation method of the composite fiber is:
[0018] Loading: adding the pretreated reed cellulose to an ethanol solution, adding ammonia water dropwise to adjust the pH to 8, stirring and mixing for 30-45 minutes, adding tetrabutyl titanate dropwise, stirring at a speed of 300-350r / min for 1-2 hours, adding trimethoxysilane (3-mercaptopropyl), placing in a hydrothermal reactor, hydrothermally reacting at a temperature of 140-180°C for 12 hours, filtering after the reaction is completed, washing the filter cake with deionized water until neutral, and drying to obtain reed fiber loaded with nano-titanium dioxide;
[0019] Composite: Add polyvinyl alcohol to deionized water, heat and stir until dissolved, add vanillin, continue to stir and mix, then add p-toluenesulfonic acid, heat to 70-80°C and keep warm for 6-8h, then add the prepared reed fiber loaded with nano-titanium dioxide, continue to stir and react for 10-12h, cool to room temperature, filter, wash the filter cake three times with anhydrous ethanol and dry to obtain composite fiber.
[0020] Furthermore, the reed cellulose is pretreated by adding the reed cellulose to a sodium hydroxide solution, heating it to 180-200° C. in a high-pressure reactor, and keeping it warm for 1-1.5 hours. After the reaction is completed, the solution is cooled to room temperature, filtered, and the filter cake is washed with deionized water until it is neutral, and then dried.
[0021] Beneficial effects of the present invention:
[0022] 1. A reed fiber biomass fully degradable lunch box of the present invention uses reed as biomass material to extract reed cellulose, and by compounding titanium dioxide on the reed cellulose, the surface of the reed cellulose becomes rougher, thereby increasing the contact area between the reed cellulose and the degradable plastic, and simultaneously in the process of compounding with the degradable plastic, a strong mechanical interlocking structure can be formed between the reed cellulose and the degradable plastic, and polyvinyl alcohol can blur the interface between the reed cellulose and the degradable plastic, enhance the interface bonding, and improve the fusion of the two, thereby increasing the mechanical properties of the degradable plastic, and the titanium dioxide generated on the surface of the reed fiber has abundant active groups, and through the grafting of vanillin, the hydrogen bonds and coordination bonds between the polyvinyl alcohol and the reed fiber can interact, thereby further improving its mechanical properties and water resistance.
[0023] 2. The reed fiber biomass fully degradable lunch box of the present invention has titanium dioxide compounded on the reed cellulose. The titanium dioxide is non-toxic and has a certain antibacterial ability, which can ensure the safety of the lunch box to a certain extent. The titanium dioxide has a photocatalytic effect and can also improve the degradation performance of degradable plastics to a certain extent.
[0024] 3. The reed cellulose of the present invention is pretreated with alkali solution, so that the dense structure of the reed cellulose becomes loose, which is more conducive to the compounding of titanium dioxide. DETAILED DESCRIPTION
[0025] The present invention will be described in detail below with reference to specific embodiments:
[0026] Embodiment 1
[0027] Extraction: The reeds were dried and ground into powder, immersed in 3 mol / L sodium hydroxide solution for 4 hours, then heated to boiling and boiled for 2 hours to obtain a cellulose solution, which was filtered and the filter cake was washed with deionized water until colorless. After dehydration, the filter cake was added into 1 mol / L sodium carbonate solution and immersed for 2 hours. After squeezing and dehydration, the solution was washed with 0.3 mol / L hydrochloric acid solution. After squeezing and dehydration, the sodium carbonate solution immersion and hydrochloric acid solution washing steps were repeated. Finally, the solution was washed with deionized water until neutral and dried at 60°C to obtain reed cellulose.
[0028] Pretreatment: Add reed cellulose to sodium hydroxide solution, heat to 200°C in a high-pressure reactor, and keep warm for 1.5 hours. After the reaction is completed, cool to room temperature, filter, wash the filter cake with deionized water until it is neutral, and dry.
[0029] Preparation of composite fibers
[0030] Loading: Add the pretreated reed cellulose to the ethanol solution, add ammonia water dropwise to adjust the pH to 8, stir and mix for 35 minutes, add tetrabutyl titanate dropwise, continue stirring at a speed of 350r / min for 2 hours, add trimethoxysilane (3-mercaptopropyl), place in a hydrothermal reactor, hydrothermally react at 180°C for 12 hours, filter after the reaction is completed, wash the filter cake with deionized water until neutral, and dry to obtain reed fiber loaded with nano-titanium dioxide;
[0031] Composite: Add polyvinyl alcohol to deionized water with a mass of 10 times that of polyvinyl alcohol, heat and stir until dissolved, add vanillin with a mass of 0.1 times that of polyvinyl alcohol, continue to stir and mix, then add p-toluenesulfonic acid with a mass of 0.01 times that of polyvinyl alcohol, heat to 70°C and keep warm for 8 hours, then add the prepared reed fiber loaded with nano-titanium dioxide, the mass ratio of polyvinyl alcohol to reed fiber is 1:3, continue to stir and react for 10 hours, cool to room temperature, filter, wash the filter cake three times with anhydrous ethanol and then dry to obtain composite fiber.
[0032] Preparation of lunch boxes
[0033] Granulation: Add 220 parts of composite fiber, 650 parts of biodegradable plastic, 15 parts of lubricant, 10 parts of antioxidant, 10 parts of dioctyl phthalate, 5 parts of glycerol, 20 parts of vinyl acetate, and 20 parts of polyvinyl alcohol into a kneader, mix for 10 minutes, and then perform plasticization, extrusion and granulation in a single screw extruder to obtain a biodegradable masterbatch.
[0034] Molding: The biodegradable masterbatch is compressed on a tablet press at 150°C, and then formed into a lunch box by a blister machine.
[0035] Embodiment 2
[0036] Extraction: The reeds were dried and ground into powder, immersed in 3 mol / L sodium hydroxide solution for 4 hours, then heated to boiling and boiled for 2 hours to obtain a cellulose solution, which was filtered and the filter cake was washed with deionized water until colorless. After dehydration, the filter cake was added into 1 mol / L sodium carbonate solution and immersed for 2 hours. After squeezing and dehydration, the solution was washed with 0.3 mol / L hydrochloric acid solution. After squeezing and dehydration, the sodium carbonate solution immersion and hydrochloric acid solution washing steps were repeated. Finally, the solution was washed with deionized water until neutral and dried at 60°C to obtain reed cellulose.
[0037] Pretreatment: Add reed cellulose to sodium hydroxide solution, heat to 190°C in a high-pressure reactor, and keep warm for 1 hour. After the reaction is completed, cool to room temperature, filter, wash the filter cake with deionized water until it is neutral, and dry.
[0038] Preparation of composite fibers
[0039] Loading: Add the pretreated reed cellulose to the ethanol solution, add ammonia water dropwise to adjust the pH to 8, stir and mix for 45 minutes, add tetrabutyl titanate dropwise, continue stirring at a speed of 300r / min for 1 hour, add trimethoxysilane (3-mercaptopropyl), place in a hydrothermal reactor, hydrothermally react at 140°C for 12 hours, filter after the reaction is completed, wash the filter cake with deionized water until neutral, and dry to obtain reed fiber loaded with nano-titanium dioxide;
[0040] Composite: Take polyvinyl alcohol and add it to deionized water with a mass of 12 times that of polyvinyl alcohol, heat and stir until dissolved, add vanillin with a mass of 0.1 times that of polyvinyl alcohol, continue to stir and mix, then add p-toluenesulfonic acid with a mass of 0.011 times that of polyvinyl alcohol, heat to 80°C and keep warm for 6 hours, then add the prepared reed fiber loaded with nano-titanium dioxide, the mass ratio of polyvinyl alcohol to reed fiber is 1:4, continue to stir and react for 12 hours, cool to room temperature, filter, wash the filter cake three times with anhydrous ethanol and then dry to obtain composite fiber.
[0041] Preparation of lunch boxes
[0042] Granulation: Add 200 parts of composite fiber, 700 parts of biodegradable plastic, 20 parts of lubricant, 5 parts of antioxidant, 20 parts of dioctyl phthalate, 8 parts of glycerol, 45 parts of vinyl acetate, and 15 parts of polyvinyl alcohol into a kneader, mix for 10 minutes, and then plasticize, extrude and granulate in a single screw extruder to obtain a biodegradable masterbatch.
[0043] Molding: The biodegradable masterbatch is compressed on a tablet press at 150°C, and then formed into a lunch box by a blister machine.
[0044] Embodiment 3
[0045] Extraction: The reeds were dried and ground into powder, immersed in 3 mol / L sodium hydroxide solution for 4 hours, then heated to boiling and boiled for 2 hours to obtain a cellulose solution, which was filtered and the filter cake was washed with deionized water until colorless. After dehydration, the filter cake was added into 1 mol / L sodium carbonate solution and immersed for 2 hours. After squeezing and dehydration, the solution was washed with 0.3 mol / L hydrochloric acid solution. After squeezing and dehydration, the sodium carbonate solution immersion and hydrochloric acid solution washing steps were repeated. Finally, the solution was washed with deionized water until neutral and dried at 60°C to obtain reed cellulose.
[0046] Pretreatment: Add reed cellulose to sodium hydroxide solution, heat to 180°C in a high-pressure reactor, and keep warm for 1.5 hours. After the reaction is completed, cool to room temperature, filter, wash the filter cake with deionized water until it is neutral, and dry.
[0047] Preparation of composite fibers
[0048] Loading: Add the pretreated reed cellulose to an ethanol solution, add ammonia water dropwise to adjust the pH to 8, stir and mix for 30 minutes, add tetrabutyl titanate dropwise, continue stirring at a speed of 350r / min for 2 hours, add trimethoxysilane (3-mercaptopropyl), place in a hydrothermal reactor, hydrothermally react at a temperature of 1600°C for 12 hours, filter after the reaction is completed, wash the filter cake with deionized water until neutral, and dry to obtain reed fiber loaded with nano-titanium dioxide;
[0049] Composite: Take polyvinyl alcohol and add it to deionized water with a mass of 11 times that of polyvinyl alcohol, heat and stir until dissolved, add vanillin with a mass of 0.1 times that of polyvinyl alcohol, continue to stir and mix, then add p-toluenesulfonic acid with a mass of 0.012 times that of polyvinyl alcohol, heat to 75°C and keep warm for 8 hours, then add the prepared reed fiber loaded with nano-titanium dioxide, the mass ratio of polyvinyl alcohol to reed fiber is 1:2, continue to stir and react for 11 hours, cool to room temperature, filter, wash the filter cake three times with anhydrous ethanol and then dry to obtain composite fiber.
[0050] Preparation of lunch boxes
[0051] Granulation: Add 250 parts of composite fiber, 650 parts of biodegradable plastic, 5 parts of lubricant, 15 parts of antioxidant, 5 parts of dioctyl phthalate, 15 parts of glycerol, 5 parts of vinyl acetate, and 60 parts of polyvinyl alcohol into a kneader, mix for 10 minutes, and then plasticize, extrude and granulate in a single screw extruder to obtain a biodegradable masterbatch.
[0052] Molding: The biodegradable masterbatch is compressed on a tablet press at 150°C, and then formed into a lunch box by a blister machine.
[0053] Comparative Example
[0054] The difference between this comparative example and Example 1 is that in this comparative example, the prepared reed cellulose is directly used to prepare a lunch box.
[0055] The lunch boxes prepared in Example 1 and the comparative example were subjected to a tensile test according to GB1040-79, a bending test according to GB1042-79, and a biodegradability test according to GB / T19277. The test results are shown in the following table:
[0056] Tensile strength / MPa Elongation at break / % Degradation rate (45 days) / % Embodiment 1 59.4 187 95 Comparative Example 45.3 164 70
[0057] It can be seen from the data in the above table that the lunch box prepared by the present invention has greatly improved mechanical properties and better degradation performance.
[0058] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention. The techniques, shapes, and structural parts not described in detail in the present invention are all known technologies.
Claims
1. A fully degradable lunch box made of reed fiber biomass. It is characterized in that The lunch box comprises the following raw materials in parts by weight: 200-250 parts of composite fiber, 650-700 parts of degradable plastic, 5-20 parts of lubricant, 20-40 parts of processing aid, and 25-100 parts of auxiliary materials. The composite fiber is reed cellulose as a carrier, titanium dioxide is generated in situ on the reed cellulose, and then composited with polyvinyl alcohol grafted with vanillin.
2. A reed fiber biomass fully degradable lunch box according to claim 1, It is characterized in that The lunch box comprises the following raw materials in parts by weight: 220 parts of composite fiber, 650 parts of degradable plastic, 15 parts of lubricant, 25 parts of processing aid, and 40 parts of auxiliary materials.
3. A reed fiber biomass fully degradable lunch box according to claim 2, It is characterized in that The degradable plastic is any one of poly(butylene adipate / terephthalate) and poly(lactic acid).
4. A reed fiber biomass fully degradable lunch box according to claim 3, It is characterized in that The auxiliary materials include 5-45 parts of vinyl acetate and 15-60 parts of polyvinyl alcohol.
5. A reed fiber biomass fully degradable lunch box according to claim 4, It is characterized in that The processing aid comprises 5-15 parts of antioxidant, 5-20 parts of dioctyl phthalate and 8-15 parts of glycerol.
6. A method for preparing a fully degradable reed fiber biomass lunch box according to any one of claims 1 to 5, It is characterized in that The preparation method is: Extraction: The reeds are dried and ground into powder, and then the reed cellulose is extracted by acid-base method to obtain reed cellulose. Then, titanium dioxide is generated in situ on the reed cellulose using the reed cellulose as a carrier, and then composited with polyvinyl alcohol grafted with vanillin to obtain composite fibers. Granulation: Add composite fiber, biodegradable plastic, lubricant, processing aid and auxiliary materials into a kneader, mix for 10 minutes, and then perform plasticization, extrusion and granulation in a single screw extruder to obtain biodegradable masterbatch; Molding: The biodegradable masterbatch is compressed on a tablet press, and then the lunch box is formed by a blister machine.
7. The method for preparing a fully degradable lunch box made of reed fiber biomass according to claim 6, It is characterized in that The extrusion temperature of the single screw extruder is 180-190° C., and the rotation speed is 30-60 r / min.
8. The method for preparing a fully degradable lunch box made of reed fiber biomass according to claim 7, It is characterized in that The preparation method of the composite fiber is: Loading: adding the pretreated reed cellulose to an ethanol solution, adding ammonia water dropwise to adjust the pH to 8, stirring and mixing for 30-45 minutes, adding tetrabutyl titanate dropwise, stirring at a speed of 300-350r / min for 1-2 hours, adding trimethoxysilane (3-mercaptopropyl), placing in a hydrothermal reactor, hydrothermally reacting at a temperature of 140-180°C for 12 hours, filtering after the reaction is completed, washing the filter cake with deionized water until neutral, and drying to obtain reed fiber loaded with nano-titanium dioxide; Composite: Add polyvinyl alcohol to deionized water, heat and stir until dissolved, add vanillin, continue to stir and mix, then add p-toluenesulfonic acid, heat to 70-80°C and keep warm for 6-8h, then add the prepared reed fiber loaded with nano-titanium dioxide, continue to stir and react for 10-12h, cool to room temperature, filter, wash the filter cake three times with anhydrous ethanol and dry to obtain composite fiber.
9. The method for preparing a fully degradable lunch box made of reed fiber biomass according to claim 8, It is characterized in that The reed cellulose is pretreated as follows: adding the reed cellulose to a sodium hydroxide solution, heating it to 180-200° C. in a high-pressure reactor, and heat-treating it for 1-1.5 hours. After the reaction is completed, cooling it to room temperature, filtering it by suction, washing the filter cake with deionized water until it is neutral, and drying it.
